Criminal Masculinities and the Newgate Novel - Richardson, Taylor R (2019)
This dissertation builds upon the seminal work of Keith Hollingsworth in his The Newgate Novel, 1830-1847 and expands analysis of the contentious Victorian subgenre into the realm of studies in masculinities. Outside of critical opinion that the novels were defined by the reactionary and conservative reception of Victorian reviewers who saw the novels as morally outrageous and socially dangerous, the genre, as this dissertation argues, was markedly concerned with specifically male readerships. Victorian critics were concerned about the effects reading criminal literature had on boys becoming men, and, accordingly, this dissertation argues that the reformative political and social climate of the 1830s and 40s was also a great period of examination and literary reflection upon the growth of the boy into the man. This dissertation considers the major canon of Newgate novels identified by Hollingsworth and includes chapters on William Godwin’s Caleb Williams and Fleetwood, Edward Bulwer-Lytton’s Paul Clifford and Eugene Aram, Charles Dickens’ Oliver Twist and Barnaby Rudge, and William Harrison Ainsworth’s Jack Sheppard. The dissertation examines how and why each of these texts is concerned with depicting, in often meticulous detail, the growth of a young male protagonist into manhood in a society that demands or necessitates his transformation into criminal. As masculinities and crime are conflated, masculinities are often essentially criminal, and criminalities often masculine. The dissertation engages with James Eli Adams’ and John Tosh’s writings on Victorian masculinities, ultimately discovering that the various masculinities depicted in Newgate novels were against established programs of self-discipline and “gentlemanliness”, instead favouring zones of literal and figurative illegality, alternative gender expression, queerness and excarceration. The novels dramatise criminal dress, male bodies, homosocial bands/bonds and societies, the penal spectacle, father-son relationships, and jailbreaking, demonstrating a need for the expression of masculinities that transcend programs of discipline and heteronormativity into the often fraught and dangerous realms of criminal-masculine excarceral jouissance, as feats of excarcerality become expressions of alternative masculinities